Implementasi Penentuan Bobot Link Menggunakan Logika Fuzzy Untuk Pencarian Jalur Terpendek Pada Software Defined Networking - Doni Hadiyansyah; Widhi Yahya; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Software-Defined Networking (SDN) is a dynamic architecture, manageable, cost-efficient, and easy to adapt. One example of a program that can be implemented on SDN is routing. One of the routing algorithm is Dijkstra's algorithm. A routing protocol using Dijkstra's algorithm is an Open Shortest Path First (OSPF). In OSPF, the cost of each link will be configured by network administrator. The administrator can choose to set all costs to 1 (Static Cost Dijkstra). The link with the the smallest hop count will be chosen without considering the presence of network traffic and delay. By using the paradigm of SDN, artificial intelligence can be implemented on a network. For that the authors have implemented a system of determining the weight of links using fuzzy logic for routing with the parameters used are traffic and delay. The results of the simulation of the system is that the system has been able to determine the cost of links for routing based on traffic and delay. Based on the results of testing the throughput, these systems have greater throughput significantly superior compared to the Static Cost Dijkstra algorithm. Then based on testing packet loss, the packet loss of this system has ranged between 0-5%, compared with Static Cost Dijkstra algorithm that has increased packet loss significant when the number of clients more than 39. But on this system have the convergence time worse then the Static Cost Dijkstra algorithm.